Serological responses to immunization during nephrosis in infants with congenital nephrotic syndrome of the Finnish type - Savonius, Okko; Kaskinen, Anu; Hölttä, Tuula; Ylinen, Elisa; Tainio, Juuso; Nieminen, Tea; Jahnukainen, Timo (Frontiers in Pediatrics, 2024)
BACKGROUND Pretransplant vaccination is generally recommended to solid organ transplant recipients. In infants with congenital nephrotic syndrome (CNS), the immune response is hypothetically inferior to other patients due to young age and urinary loss of immunoglobulins, but data on the immunization response in severely nephrotic children remain scarce. If effective, however, early immunization of infants with CNS would clinically be advantageous. METHODS We investigated serological vaccine responses in seven children with CNS who were immunized during nephrosis. Antibody responses to measles-mumps-rubellavaccine (MMR), a pentavalent DTaP-IPV-Hib -vaccine (diphtheria, tetanus, acellular pertussis, inactivated poliovirus, Haemophilus influenzae type b), varicella vaccine, combined hepatitis A and B vaccine, and pneumococcal conjugate vaccine (PCV) were measured after nephrectomy either before or after kidney transplantation. RESULTS Immunizations were started at a median age of 7 months (interquartile range [IQR] 7-8), with a concurrent median proteinuria of 36500 mg/L (IQR 30900-64250). Bilateral nephrectomy was performed at a median age of 20 months (IQR 14-25), and kidney transplantation 10-88 days after the nephrectomy. Antibody levels were measured at median 18 months (IQR 6-23) after immunization.Protective antibody levels were detected in all examined children for hepatitis B(5/5), Clostridium tetani (7/7), rubella virus (2/2), and mumps virus (1/1); in 5/6 children for varicella; in 4/6 for poliovirus and vaccine-type pneumococcal serotypes; in 4/7 for Haemophilus influenzae type B and Corynebacterium diphtheriae; in 1/2 for measles virus; and in 2/5 for hepatitis A. None of the seven children had protective IgG levels against Bordetella pertussis. CONCLUSION Immunization during severe congenital proteinuria resulted in variable serological responses, with both vaccine-and patient-related differences. Nephrosis appears not to be a barrier to successful immunization.